Glycoprotein 130-dependent pathways in host hepatocytes are important for liver repopulation in mice - Tschaharganeh, Darjus-Felix; Kaldenbach, Michaela; Erschfeld, Stephanie; Tischendorf, Jens J. W.; Trautwein, Christian; Streetz, Konrad L. (Liver transplantation, 2010)
Hepatocyte transplantation (HT) is still restricted by the limited amount of transplantable cells. Therefore, a better understanding of the mechanisms involved in cellular engraftment, proliferation, and in vivo selection is important. Here we aimed to evaluate the role of the interleukin 6 (IL-6)/glycoprotein 130 (gp130) system for liver repopulation. Mice carrying a conditional hepatocyte-specific deletion of the common IL-6 signal transducer gp130 (gp130Δhepa) were used for HT. First, we compared bone marrow transplantation (BMT), partial hepatectomy (PH), and retrorsine treatment of recipient mice to optimize the in vivo selection of transplanted hepatocytes. BMT combined with PH was sufficient to induce a 30-fold increase in the number of transplanted donor hepatocytes, whereas additional retrorsine pretreatment led to an up to 40-fold increase. Next, the influence of gp130 signaling in hepatocytes on cell selection was evaluated. Wild-type (WT) hepatocytes repopulated WT recipients at the same rate as gp130Δhepa cells. In contrast, liver repopulation by transplanted cells was enhanced in gp130Δhepa recipient mice. This was associated with higher proliferation of donor hepatocytes and enhanced apoptosis in gp130Δhepa recipient livers. Additionally, the acute phase response was strongly induced after HT in WT recipients but blunted in gp130Δhepa recipients. As a result, significantly more liver remodeling, evidenced by stronger hepatic stellate cell activation and collagen accumulation, was found in gp130Δhepa mice after HT. In conclusion, the HT model established here can be efficiently applied to investigate cell-specific mechanisms in liver repopulation. Moreover, we have shown that gp130-dependent pathways in host hepatocytes are important for controlling liver repopulation. Liver Transpl 16:23-32, 2010. © 2009 AASLD.
Erstmals am 23 December 2009 online erschienen
Gesehen am 19.01.2024